The Role of Conjunction in Achieving Coherence of Duaa Al-Nadba:Semantic and Grammatical Study - Aind Tamal , Lect. Dr.Muntaha (Basra studies journal, 2022)
The research aims mainly and directly to study objective interdependence by using conjunctions, and its effect on achieving textual cohesion in Duaa Al Nadba, also revealing the text of the prayer of the wellness of syntactic and semantic structure based on modern textual bases. Which differs from the old view that was limited to looking at the sentence only compared to the modern textual study that expanded in its view of the text through the study of the whole text. The study shed lights on links between sentences, their sequences, and their manifestations of harmony, and their contribution to clarifying the purpose or purpose of their mention in the text of different types, which contributes to the study of the links between sentences, their sequences, and their manifestations of harmony, and their contribution to explaining the purpose of their mention in the text. this contributed in achieving verbal and moral cohesion in the overall structure of the text through the sequence of its topics and diversity and casting them into a specific subject with a specific purpose and purpose that the Imam wanted to convey to the recipient.